Multiparametric Study of Water–Gas Shift and Hydrogen Separation Performance in Membrane Reactors Fed with Biomass-Derived Syngas - Nadia Cerone; Luca Contuzzi; Giuseppe Domenico Zito; Carmine Florio; Laura Fabbiano; Francesco Zimbardi (Hydrogen)
A multiparametric study was conducted on a hydrogen (H2) production rig designed to process 0.25 Nm3·h−1 of syngas. The rig consists of two Pd-Ag membrane permeator units and two Pd-Ag membrane reactor units for the water–gas shift (WGS) reaction, enabling a detailed and comprehensive analysis of its performance. The aim was to find the optimal conditions to maximize hydrogen production by WGS and its separation in a pure stream by varying the temperature, pressure, and steam-to-CO ratio (S/CO). Two syngas mixtures obtained from an updraft gasifier using different gasification agents (air–steam and oxy–steam) were used to investigate the effect of gas composition. The performance of the rig was investigated under nine combinations of temperature, pressure, and S/CO in the respective ranges of 300–350 °C, 2–8 bar, and 1.1–2 mol·mol−1, as planned with the help of design of experiment (DOE) software. The three parameters positively affected performance, both in terms of capacity to separate a pure stream of H2, reported as moles permeated per unit of surface area and time, and in producing new H2 from WGS, reported as moles of H2 produced per volume of catalyst unit and time. The highest yields were obtained using syngas from oxy–steam gasification, which had the highest H2 concentration and was free of N2.